Successful Application of Maggot Debridement Therapy (MDT) on a Fournier’s Gangrene - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Fournier’s gangrene is a rapidly progressing soft tissue infection and a urological emergency affecting the external genitalia or the perineum. Maggot debridement therapy (MDT) has resurfaced as a result of the steep rise in the emergence of antibiotic-resistant strains of pathogenic bacteria and the need for an effective non-surgical method for wound debridement. This case study reports on a 66-year-old known diabetic who presented to our facility with complaints of scrotal swelling and multiple foul-smelling ulcers around the genital area. There was associated history of pain and fever for twelve-day duration. Sterile first instar larvae ofL. sericatawere applied using the free-ranged method. Significant decrease in the peri-wound oedema, rapid epithelization and increased vascularity were observed in the patient after the therapy. Maggot debridement therapy was successfully used in the debridement of Fournier’s gangrene in Nigeria for the first time, and the clinical outcome is encouraging.